A Population-Based Study of COVID-19 Infection Among Childhood Cancer Survivors - Agha, Mohammad; Leung, Felicia; Moineddin, Rahim; Bradley, Nicole M.; Gibson, Paul J.; Hodgson, David C. (Frontiers in Medicine, 2021)
Childhood cancer survivors are known to be at risk of chronic co-morbidities, although their risk of COVID-19 infection remains uncertain. Understanding the risk of COVID-19 in this population is necessary to counsel survivors and inform potential mitigation strategies. The objective of this study was to determine whether the rates of COVID-19 infection differed between childhood cancer survivors and the general population. Administrative health care data from a population-based registry of children and adolescents diagnosed with cancer in Ontario, Canada, were linked with a universal health insurance registry and a repository of laboratory data. Rates of COVID-19 testing, test positivity and infection between March 1, 2020 and January 31, 2021 among childhood cancer survivors (n=10 242) were compared to matched controls from the general population (n=49 068). Compared to the general population, childhood cancer survivors were more likely to have COVID-19 testing (28.5% [95% CI, 27.3%-29.7%] vs. 24.4% [95% CI, 23.9%-24.9%]), but had a lower likelihood of positive COVID-19 result among those tested (3.0% [95% CI, 2.3%-3.6%] vs. 4.2% [95% CI, 3.8%-4.6%]) and a similar rate of infection among all subjects at risk (0.8% [95% CI, 0.7%-1.0%] vs. 1.0% [95% CI, 0.9%-1.1%]). These findings can inform counselling of survivors and clinician recommendations for this population.